Dignity Therapy and the past That Matters: Dialogues with Older People on Values and Photos. Issue 1 (2nd January 2022) - Testoni, Ines; D'Ippolito, Mino; Iacona, Erika; Zamperini, Adriano; Mencacci, Elisa; Chochinov, Harvey M.; Grassi, Luigi
Abstract: Objectives: Dignity therapy (DT) is recognized as a valid form of support for terminally ill patients who have to manage trauma and loss. Given the positive evidence associated with DT, finding ways of adapting it for the older people warrants consideration. Methods: The study examines if DT can be improved with the use of an album of family photographs, in order to process the sense of loss of dignity and past traumas. Sixteen institutionalized participants were surveyed, via mixed methods. Results: Quantitative data were collected with the help of the Patient Dignity Inventory, and the qualitative analysis was based on generativity documents. Conclusion: Results confirmed the feasibility of this approach for this cohort.